Intervensi Gizi oleh Pemerintah Daerah Sebagai Upaya untuk Mempercepat Pengurangan Stunting - Erlyn, Putri; Hidayat, Bachtari; Fatoni, Agus; Saksono, Herie (Research and Development Agency Ministry of Home Affairs, 2021)
Nutritional problems, known as stunting, are a major threat to the quality of Indonesian society that interferes with children's physical growth and brain development disorders that will affect their achievement. This study aims to analyze the nutrition intervention program and program achievements carried out by the Palembang City government. The research method used is qualitative research with a descriptive approach. This study uses secondary data from the Palembang City Health Office to measure the number of short toddlers taking measurements in the October 2021 period. This is continued by describing the achievements of the nutrition intervention program that has been carried out by the Palembang City government and analyzing the problems that exist in the stunting program in Palembang City using the SWOT method. This study found that specific nutrition interventions were carried out through health programs while sensitive nutrition interventions were carried out through environmental programs. In an effort to reduce stunting in the city of Palembang, the strengths are stunting data collected by name by address and program innovations run at health centers. However, the weakness is that there is not optimal coordination and program synergy between related agencies. Low community motivation and lack of knowledge related to child-rearing patterns are a challenge, but the Palembang City government's commitment, as stated in the Mayor's Regulation policy, becomes the basis and direction of policy in designing stunting reduction and programs for the next five years.